Highway 12 - Probasco, Christian, author; Utah State University Press, publisher (Colorado State University. Libraries, 2005)
Highway 12 is undoubtedly one of not only America's but the world's most scenic highways. From its intersection on the west with Highway 89 south of Panguitch, Utah, it runs up through Red Canyon onto the Paunsagunt Plateau and across Bryce Canyon National Park. It then drops into the Paria River Valley, passes through several tiny villages, crosses some extraordinary (for anywhere but this region) badlands, and descends the Escalante River into Potato Valley. While a driver may justifiably feel she has seen some scenery by that point, the highway is just getting started, for in the next stretch, it crosses a labyrinth of multicolored sandstone humps and corridors, climaxed by a narrow hogback with steep slickrock drops to each side, all within Grand Staircase-Escalante National Monument. Reaching the oasis of Boulder within this desert of rock, the road then climbs across the flank of the Aquarius Plateau, providing spectacular vistas and terminating at the gateway to Capitol Reef National Park. Along the way side roads and trails access the vast wilderness of the Paria and Escalante Rivers and the high plateaus they drain. Congress acknowledged the unequaled splendor of Highway 12 by designating it one of a handful of All-American Roads. To travel with Christian Probasco this road and its spurs, which lead deep into some of the wildest, most broken-up and stunning landscapes anywhere, can put a unique twist on an already singular experience. He knows the region as well as anyone and brings an original, edgy, youthful view to it. His opinions and his language may challenge you. His approaches to and perspectives on the land may sometimes surprise you. His understanding of the area's history and its people will likely teach you a thing or two.
Chapter One. Hoodoo Lands and the Rim -- Chapter Two. The Western Spokes -- Chapter Three. Hard Roads -- Chapter Four. The Eastern Rim, the Eastern Spokes and the Hub.
Keywords: Automobile travel -- Utah -- Guidebooks; Utah -- Guidebooks; Utah -- Description and travel; United States Highway 12 -- Guidebooks; Grand Staircase-Escalante National Monument (Utah) -- Description and travel; Bryce Canyon National Park (Utah) -- Description and travel; Capitol Reef National Park (Utah) -- Description and travel